2018
DOI: 10.1002/ece3.4504
|View full text |Cite
|
Sign up to set email alerts
|

Methylation divergence of invasive Ciona ascidians: Significant population structure and local environmental influence

Abstract: The geographical expansion of invasive species usually leads to temporary and/or permanent changes at multiple levels (genetics, epigenetics, gene expression, etc.) to acclimatize to abiotic and/or biotic stresses in novel environments. Epigenetic variation such as DNA methylation is often involved in response to diverse local environments, thus representing one crucial mechanism to promote invasion success. However, evidence is scant on the potential role of DNA methylation variation in rapid environmental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 88 publications
(178 reference statements)
2
13
0
Order By: Relevance
“…Biological invasions provide an excellent "natural experiment" to study how species cope with environmental stresses, as invasive species encounter sudden, and often repeated, extensive environmental challenges during the invasion process (Zhan et al, 2015;Ni et al, 2018). Particularly for human activity-mediated introductions, invasive species often encounter environmental changes much greater and/or faster than what species can experience under natural conditions such as seasonal fluctuations (Zhan et al, 2015;Chen et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Biological invasions provide an excellent "natural experiment" to study how species cope with environmental stresses, as invasive species encounter sudden, and often repeated, extensive environmental challenges during the invasion process (Zhan et al, 2015;Ni et al, 2018). Particularly for human activity-mediated introductions, invasive species often encounter environmental changes much greater and/or faster than what species can experience under natural conditions such as seasonal fluctuations (Zhan et al, 2015;Chen et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…vexillum (New Zealand), but not in the native range (Japan). Recent studies of invasive populations have found DNA methylation differences between environments that may play a role in adaptation to different habitats 49,76,77 . In the present study, comparisons of DNA methylation patterns between sites with similar or different environmental stress (temperature and salinity) scores indicate that DNA methylation patterns are not driven by environmental variations alone.…”
Section: Discussionmentioning
confidence: 99%
“…Only the sites hosting lineage C are not completely isolated from each other, but M04 and M05 are still 3.6 km apart and separated by a road and grasslands, which are typically avoided by Ambystoma salamanders [39]. Salamanders from the genus Ambystoma display strong fidelity to their breeding sites [40], and the dispersing individuals move on average only 150 m from their breeding ponds during breeding season, and rarely over 300 m [32, 39–42].…”
Section: Discussionmentioning
confidence: 99%